Business communication : a framework for success - O'Hair, H. Dan; O'Rourke, James S.; O'Hair, Mary John (Australia : South-Western College Publishing / Thomson Learning, 2001)
Business
Keywords: Business communication; Business speaking; Business writing; Organizational communication; Correspondence